Aicardi's diseases of the nervous system in childhood - Arzimanoglou, Alexis; O'Hare, Anne; Johnston, Michael V.; Ouvrier, R. A. (Robert A.) (Clinics in developmental medicine., 2018)
The fourth edition of this unique text, provides comprehensive information on paediatric neurological disorders in a clinical, user-friendly context.